Effects of Partners Together in Health Intervention on Physical Activity and Healthy Eating Behaviors: A Pilot Study. Issue 2 (March 2015) - Yates, Bernice C.; Norman, Joseph; Meza, Jane; Krogstrand, Kaye Stanek; Harrington, Susana; Shurmur, Scott; Johnson, Matthew; Schumacher, Karen
Abstract : Background: Despite proven efficacy of cardiac rehabilitation (CR) in helping patients initiate physical activity and healthy eating changes, less than 50% of CR participants maintain changes 6 months later. Objective: The objective of this feasibility study was to test the Partners Together in Health (PaTH) intervention versus usual care in improving physical activity and healthy eating behaviors in coronary artery bypass graft surgery patients and their spouses. Methods: An experimental, 2-group (n = 17 couples/group), repeated-measures design was used. Coronary artery bypass surgery patients in both groups participated in phase II outpatient CR. Spouses in the PaTH group attended CR with the patient and were asked to make the same physical activity and healthy eating changes as patients did. Spouses in the usual care attended educational classes with patients. It was theorized that "2 persons would be better than 1" at making changes and sticking with them in the long-term. Physical activity behavior was measured using the Actiheart accelerometer; the activity biomarker was an exercise tolerance test. Eating behavior was measured using 3-day food records; the biomarker was the lipid profile. Data were collected at baseline (entrance in CR), at 3 months (post-CR), and at 6 months. Changes over time were examined using Mann-Whitney U statistics and effect sizes. Results: The PaTH intervention was successful primarily in demonstrating improved trends in healthy eating behavior for patients and spouses. No differences were found between the PaTH and usual care patients or spouses at 3 or 6 months in the number of minutes per week of physical activity. By 6 months, patients in both groups were, on average, below the national guidelines for PA recommendations (≥150 min/wk at >3 metabolic equivalents). Conclusions: The couple-focused PaTH intervention demonstrated promise in offsetting the decline in dietary adherence typically seen 6 months after CR.